Archaeological excavations in Moneen Cave, the Burren, Co. Clare : insights into Bronze Age and post-medieval life in the West of Ireland - Dowd, Marion (Archaeopress, 2016)
In 2011, cavers exploring a little-known cave on Moneen Mountain in County Clare in the west of Ireland discovered part of a human skull, pottery and an antler implement. An archaeological excavation followed, leading to the discovery of large quantities of Bronze Age pottery, butchered animal bones and oyster shells.